2016
DOI: 10.1007/s11274-016-2133-1
|View full text |Cite
|
Sign up to set email alerts
|

Vertical zonation of soil fungal community structure in a Korean pine forest on Changbai Mountain, China

Abstract: Changbai Mountain, with intact montane vertical vegetation belts, is located at a sensitive area of global climate change and a central distribution area of Korean pine forest. Broad-leaved Korean pine mixed forest (Pinus koraiensis as an edificator) is the most representative zonal climax vegetation in the humid region of northeastern China; their vertical zonation is the most intact and representative on Changbai Mountain. In this study, we analyzed the composition and diversity of soil fungal communities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 30 publications
7
21
0
Order By: Relevance
“…Previous studies have observed different elevational patterns in soil fungal diversity. For example, Ping et al (2017) found that soil fungal diversity decreased between the elevations from 699 to 937 m but increased between 937 and 1044 m in Korean pine forests on Changbai Mountain, showing a hollow curve’s pattern. Yang et al (2017c) observed a monotonic decrease in soil fungal diversity along elevation from 700 to 2600 m by the culture-dependent method on Changbai Mountain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have observed different elevational patterns in soil fungal diversity. For example, Ping et al (2017) found that soil fungal diversity decreased between the elevations from 699 to 937 m but increased between 937 and 1044 m in Korean pine forests on Changbai Mountain, showing a hollow curve’s pattern. Yang et al (2017c) observed a monotonic decrease in soil fungal diversity along elevation from 700 to 2600 m by the culture-dependent method on Changbai Mountain.…”
Section: Discussionmentioning
confidence: 99%
“…At a large-scale elevational mountain gradient, Shen et al (2014) found that although soil eukaryotic microbial richness was not correlated with elevation, it was strongly correlated with soil pH on the Changbai Mountain, China. However, Ping et al (2017) observed on the same mountain that soil fungal richness and evenness decreased with the increasing elevation gradient, and the community composition was significantly influenced by soil C/N ratio, moisture, pH, and total nitrogen (TN), suggesting that this elevational diversity pattern was scale dependent.…”
Section: Introductionmentioning
confidence: 98%
“…Because vegetation types determine litter composition and soil C/N ratio, then affect microbial community structure (Djukic et al., ; Singh, Shi, & Adams, ). We discovered a gradual change in the plant composition at the elevation of 1,044 m, the presence of coniferous trees increased (Ping et al., ), the litter composition changed then had an impact on soil bacterial community.…”
Section: Discussionmentioning
confidence: 99%
“…Taxonomy analysis was assigned to OTUs (at the level of 97% similarity) against Silva database, using the RDP classifier Jest algorithm in QIIME (Ping et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation